ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP MINAT BELI SMARTPHONE - Christiandy Christiandy; Herlin Hidayat (Prosiding Working Papers Series In Management, 2018)
Smartphones are growing rapidly and are used as a tool to meet the needs of the world community, including Indonesia. The number of smartphone users, especially those who use Android Operating System as much as 78% in 2013. Many enthusiasts and smartphone users, encourage manufacturers to provide better quality products at affordable prices and accentuate their brand image. The purpose of this study is to analyze the effect of product quality, price and brand image on intention to buy. The data used are primary data and the population in this study are students and workers. Distribution of questionnaires with convenience sampling method to 100 respondents. The results showed that there was an effect of product quality on intention to buy, there were effects of prices on intention to buy, there was an influence of brand image on intention to buy, and there was an influence of product quality, price and brand image on smartphone intention to buy. Keywords: product quality, price, brand image, intention to buy